Holy Spirit : works & gifts - Bloesch, Donald G., 1928-2010 (Illinois : Downers Grove IVP Acadenic, 2000)
"In The Holy Spirit: Works & Gifts Donald Bloesch aptly brings together his grasp of historical and systematic theology as well as his deep concern for spirituality. The fruit of a lifetime of study and devotion, this book masterfully interweaves biblical study, historical overviews and reflection on contemporary developments and issues to shed light on faith in God, the Holy Spirit. On a topic that sadly threatens to divide the church, Bloesch strives to build bridges between the various traditions of Christian faith, especially between Reformed theology and the Pentecostal movement. This wide-ranging and in-depth reflection on the presence, reality and ministry of the Holy Spirit serves as a landmark guide to those seeking a faithful theological understanding of the Holy Spirit as well as those searching for a renewing and enpowering hope for the church of Jesus Christ" --Page 4 of cover.
Introduction -- The contemporary debate -- The descent of the Spirit in biblical understanding -- Fathers, enthusiasts & mystics -- Reformation perspectives -- Post-Reformation renewal movements -- New challenges to traditional faith -- Pentecostalism -- Recent developments in theological thought -- The Holy Spirit: person & mission -- The highway of holiness.
Includes bibliographical references (pages 343-396) and indexes.
Keywords: Holy Spirit; Gifts, Spiritual